Development of Web-Based Goods Inventory Information System to Improve Efficiency and Effectiveness of Inventory Management at Batam Cable Vision Company - Willya Kusuma; Novi Hendri Adi; Afrina; John Rey A. Jimenez (Journal of Computer-based Instructional Media, 2023)
Batam Cable Vision is a company engaged in cable TV and internet installation services. This company has problems in data processing which results in different quantities of goods. So that a system is needed that can determine the amount of inventory in the warehouse. Therefore, a web-based inventory system is designed to find out the exact amount of inventory and can be accessed via the internet. This research is designed using the waterfall method, there are five stages, namely planning is the process of designing a system like what will be made, analysis is understanding the existing system with the system to be created, system design is carried out with the aim of helping to provide a complete picture of what to do, coding is the process of writing program code, then checking and testing the system as a whole to identify possible system failures and errors, in the last stage maintenance includes error correction, improvement of system unit implementation, and system improvement and adjustment according to user needs. While the modelling used uses the Unified Modeling Language (UML) which consists of a use case diagram, activity diagram, class diagram and sequence diagram. The result of this research is a web-based inventory information system at PT Batam Cable Vision is expected to help the admin in data processing, in order to minimise errors in recording goods. Then, the inventory information system can present the right goods report information according to company needs so as to minimise the use of paper.